From East to West: Accessibility and Bias in Self–Other Comparative Judgments. (November 2014) - Christian, Colton B.; Lee, I-Ching; Hodges, Sara D.
People often weight information about the self more heavily than information about other people when making social comparative judgments. One possible explanation for this egocentrism is that information about the self is more accessible than information about others. We examine this egocentrism in samples from the United States and Taiwan. Study 1 finds egocentrism in comparisons of the self with the average other person in both cultures. Study 2 measured reaction times, demonstrating that (a) information about the self is more accessible than information about the average other and (b) as the accessibility of self-information increases, so does the influence of that information. Study 3 replicates Study 2, using comparisons with a specific other person. Egocentrism occurred in both cultures, suggesting that heavier weighting of self-information occurs across the traditional East–West cultural divide.